The Relationship between the Therapy Cycle and the Success of Patent Ductus Arteriosus Closure Treatment in Premature Babies - Amelia, Putri; William Chandra Wijaya; Pandaibesi, Robby (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2025)
Patent Ductus Arteriosus (PDA) is a disease often found in premature babies characterized by failure or delay in the closure of the Ductus Arteriosus (DA). PDA frequently occurs in babies born prematurely and is caused by high levels of prostaglandin E2 (PGE2) due to incomplete closure of the ductus and lung function. This condition can disrupt hemodynamics, so it needs to be closed. Closure can be done using cyclooxygenase (COX) inhibitor drugs, such as Indomethacin and Ibuprofen. Apart from that, paracetamol can also be used as an alternative to trigger the closure of the PDA. This study aims to establish the correlation between the medical intervention cycle and the efficacy of closing Patent Ductus Arteriosus (PDA) in preterm infants. The investigation employed an observational, retrospective, analytical approach along with a cross-sectional layout. The sampling technique in this research was total sampling. The sample obtained was 24 newborns, which was secondary data in the form of medical records obtained at the medical records installation of RSUP Haji Adam Malik Medan and Mother and Child Stella Maris Hospital Medan. All data were then processed and analyzed, and statistical tests were carried out using Spearman correlation tests with the SPSS application. The outcomes of this investigation, utilizing the Spearman correlation analysis, revealed a significant value of p = 0.001 (p<0.05) concerning the association between the duration of treatment and treatment efficacy and a significant value of p = <0.001 (p<0.05) concerning the treatment cycle and treatment efficacy. Thus, there was no relationship between the treatment cycle and the success of the treatment.